2017
DOI: 10.1016/j.je.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frailty in Japan: A systematic review and meta-analysis

Abstract: Japan's population is aging more rapidly than that of any other country. Frailty has recently been recognized as an important priority. Understanding the basic epidemiology of frailty in Japan, which is an example of a rapidly aging society, will be beneficial for Japan as well as other countries expecting an aging population. A systematic literature search of 11 electronic databases was conducted in March 2016 using a comprehensive set of Medical Subject Heading and text terms for any studies published in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
227
8
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(256 citation statements)
references
References 38 publications
17
227
8
4
Order By: Relevance
“…The results of the 5-COOP study confirm that frailty involves a majority of centenarians in a much larger sample and are in line with the above-mentioned studies [9,15,20,24]. This very high prevalence of frailty in centenarians raises the question of whether an additional category corresponding to people having 4-5 frailty criteria should be distinguished in order to discriminate "very frail" or "super-frail" people from frail people (still not dependent in ≥2 ADL for 25% of them).…”
Section: Prevalence and Characteristics Of Frailtysupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the 5-COOP study confirm that frailty involves a majority of centenarians in a much larger sample and are in line with the above-mentioned studies [9,15,20,24]. This very high prevalence of frailty in centenarians raises the question of whether an additional category corresponding to people having 4-5 frailty criteria should be distinguished in order to discriminate "very frail" or "super-frail" people from frail people (still not dependent in ≥2 ADL for 25% of them).…”
Section: Prevalence and Characteristics Of Frailtysupporting
confidence: 88%
“…A Spanish study reported that phenotypic frailty was present in 21% of 273 community-dwelling people aged 86 years participating in a clinical trial [23]. A meta-analysis of Japanese studies estimated the prevalence of frailty at 35% among 407 community-dwelling people aged 85 years and over [24]. A French study among 512 nonagenarians reported that 54% of the participants met the criteria for frailty, in the absence of disability in half of them [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty affects almost 1 in every 2 patients with heart failure [2], whereas only 7.4–10.7% of community-dwelling older adults were identified as frail [3, 4]. Physical frailty results in elevated rates of mortality, morbidity, functional decline, and major adverse cardiac and cerebrovascular events following cardiac surgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis [2] identified five studies incorporating 11,940 Japanese people aged 65 years or older living in the community and demonstrated that the pooled prevalences of frailty, prefrailty, and robustness based on the Fried criteria were 7.4, 48.1, and 44.4%, respectively. Stratified analyses showed that women were frailer than men and that prevalence of frailty increased with age.…”
Section: Introductionmentioning
confidence: 99%